Sistem Pengendalian Manajemen dan Proactive Working Behavior - Nindhika Rina Ayuning Aji (Jurnal Akuntansi Bisnis, 2019)
This study examines the moderating effect of flexible role orientation on the relationship between lack of controllability dan proactive work behaviour. Flexible role orientation encourages proactive cognitive motivational states. When employees feel flexible in role orientation, they feel more responsibility for organizational goals. On the other hand, managers who feel inferior in their level of responsibility will form a narrow role with a rigid role orientation. Flexible roles describe cognitive conditions that arise from the need to achieve a higher level of organizational responsibility. This study replicates Burkert et a.l's research additional external variabels. This research uses managers of manufacturing companies in the city of Semarang. The data analysis employs linear regression technique and Sobel Test. Results show that flexible role orientation can mediate the relationship between lack of controllability and proactive work behavior Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh keberadaan sistem pengendalian manajemen terhadap proactive work behaviour. Orientasi peran yang fleksibel mendorong motivasi kognitif proaktif dan kontras dengan keadaan pasif. Ketika karyawan merasakan orientasi peran yang fleksibel, mereka merasakan lebih banyak tanggung jawab untuk tujuan organisasi. Penelitian ini mereplikasi riset Burkert et al. (2016) dengan menambah variabel eksternal. Sampel yang digunakan adalah manager yang bekerja pada perusahaan-perusahan manufaktur di kota Semarang. Teknik analisis data adalah regresi linear dan Sobel Test. Hasil penelitian menunjukkan flexible role orientation dapat memediasi hubungan antara lack of controllability dan proactive work behaviour